Endovascular Therapy in Ischemic Stroke With Acute Large‐Vessel Occlusion: Recovery by Endovascular Salvage for Cerebral Ultra‐Acute Embolism Japan Registry 2. Issue 9 (13 September 0207) - Yoshimura, Shinichi; Sakai, Nobuyuki; Uchida, Kazutaka; Yamagami, Hiroshi; Ezura, Masayuki; Okada, Yasushi; Kitagawa, Kazuo; Kimura, Kazumi; Sasaki, Makoto; Tanahashi, Norio; Toyoda, Kazunori; Furui, Eisuke; et al.
Abstract : Background: Endovascular therapy has been shown to be effective in patients with acute cerebral large‐vessel occlusion, but real‐world efficacies are unknown. Methods and Results: We conducted a prospective registry at 46 centers between October 2014 and January 2017. Eligible patients were those who were aged 20 years or older, with acute cerebral large‐vessel occlusion, and who were hospitalized within 24 hours of the onset. We enrolled both consecutive patients who were treated with or without endovascular therapy. Endovascular therapy included thrombectomy, balloon angioplasty, stenting, local fibrinolysis, and piercing. The primary outcome was a favorable outcome as defined by a modified Rankin Scale of 0 to 2 at 90 days after onset. Secondary outcomes were modified Rankin Scale of 0 to 1 and mortality. Safety outcomes were intracerebral hemorrhage or a recurrence of ischemic stroke. We constructed the 2242 (1121 each) propensity score–matched patients cohort based on a propensity score for endovascular therapy and estimated the adjusted odds ratio, followed by sensitivity analyses on original 2399 (1278 in endovascular therapy versus 1121 in no endovascular therapy) patients. In the propensity score–matched cohort, favorable outcomes were observed in 35.3% and 30.7% of patients in the endovascular therapy and no endovascular therapy groups, respectively ( P= 0.02). The adjusted odds ratio for the favorable outcome was 1.44 (95% confidence interval, 1.10–1.86, P =0.007). The efficacy of endovascular therapy in achieving favorable outcomes did not differ between our subgroups and in the sensitivity analyses. Conclusions: Endovascular therapy decreased disabilities at 90 days in real‐world patients with acute cerebral large‐vessel occlusion. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02419794.